Potential vorticity structure of Titan’s polar vortices from Cassini CIRS observations - Sharkey, J; Teanby, NA; Sylvestre, M; Mitchell, DM; Seviour, WJM; Nixon, CA; Irwin, PGJ (Elsevier, 2020)
The Cassini mission has provided the best opportunity to date to extensively study the seasonal variation in Titan’s atmosphere, with observations spanning almost half a Titan year (). An important feature in the Titan middle-atmosphere is the formation of a polar vortex. Observations have shown that an initially well-developed northern vortex enriched with trace gas species gradually breaks down after spring equinox as a new vortex emerges in southern winter. Here we use Cassini CIRS observations to derive the temperature and composition of the middle-atmosphere. We use the gradient wind equation to first estimate the mean zonal winds, and then the Potential Vorticity (PV) throughout Titan’s atmosphere over the timespan of the Cassini mission. PV is a useful diagnostic quantity for studying the dynamics of polar vortices because it is materially conserved for adiabatic and frictionless flows, and can be inverted to find all other dynamical fields. Our results show the formation of a strong zonal jet in the winter hemisphere, with wind velocities reaching 220 ms, which is consistent with previous studies. An annular PV structure is also observed over the winter poles, whereby a ring of PV encircles a local minima over the pole. Such distributions are often found to be unstable without a restoring force, yet they are seen here in numerous observations in both the northern and southern hemispheres. A comparison with the annular Martian vortices shows that latent heat release from condensation or subsidence-induced adiabatic heating may explain the origin and stability of the annulus. Finally, we investigate the evolution of the size of the vortices and the role of strong PV gradients as a dynamical mixing barrier for trace gas species across the vortex edge. We find that longer lived gases are less confined to the vortex than those with shorter photochemical lifetimes.